2006
DOI: 10.1063/1.2221504
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer etching of InP using a low angle forward reflected Ne neutral beam

Abstract: In this study, the atomic layer etching characteristics and the etch mechanism of ͑100͒ InP as functions of Cl 2 pressure and Ne neutral beam irradiation dose were investigated. When Cl 2 pressure and Ne neutral beam irradiation dose were lower than the critical values of 0.4 mTorr and 7.2 ϫ 10 15 at./ cm 2 cycle, respectively, the InP etch rate ͑Å/cycle͒ and the InP surface roughness varied with Cl 2 pressure and Ne neutral beam irradiation dose. However, when the Cl 2 pressure and Ne neutral beam irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 5 publications
0
46
0
Order By: Relevance
“…Park et al 69,70 studied ALE of InP and InAlAs based on 20 s exposure to Cl 2 at 0.4 mTorr, followed by Ne neutral beam bombardment. They measured roughly 1 monolayer /cycle (1.47 A/cycle) for InP with high selectivity against InAlAs (0.02 A/cycle), and observed no significant surface compositional changes.…”
Section: Iii-v: Gaasmentioning
confidence: 99%
“…Park et al 69,70 studied ALE of InP and InAlAs based on 20 s exposure to Cl 2 at 0.4 mTorr, followed by Ne neutral beam bombardment. They measured roughly 1 monolayer /cycle (1.47 A/cycle) for InP with high selectivity against InAlAs (0.02 A/cycle), and observed no significant surface compositional changes.…”
Section: Iii-v: Gaasmentioning
confidence: 99%
“…Using this approach, ALEt has been reported for Si, 2,3,[8][9][10][11][12] Ge, 6,13 and compound semiconductors. [14][15][16][17] ALEt has also been demonstrated for a variety of metal oxides. 7,[18][19][20] Additional ALEt studies have been conducted on various carbon substrates.…”
mentioning
confidence: 99%
“…For example, Metzler et al 2 have reported such a mechanism to remove an atomic layer of SiO 2 using a combination of C 4 F 8 plasma to create a surface fluorocarbon (FC) layer followed by an ion bombardment with low-energy Ar + ions to remove the surface FC layer. Park et al 3 have reported a similar mechanism for atomic z E-mail: satyarth.suri@intel.com layer removal of Si using a combination of Cl 2 adsorption and Ne neutral beam. Such atomic layer etching processes have also been reported for GaAs 5 and Ge.…”
Section: What Is Atomic Layer Etching?mentioning
confidence: 97%
“…They have demonstrated InP recess stopping on an InAlAs/InGaAs transistor channel. 3,4 The benefit of the ALEt process was observed by fabricating transistors with superior Hall mobilities relative to devices patterned with conventional plasma processes. They have also used a Ne neutral beam for ALEt of GaAs and demonstrated preservation of the surface stoichiometry, which was not achieved through a continuous ICP plasma etch.…”
Section: Potential Applications For Atomic Layer Etchingmentioning
confidence: 99%
See 1 more Smart Citation